2022
DOI: 10.48550/arxiv.2210.17161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Cause-of-Death Classification from Verbal Autopsy Reports

Abstract: In many lower-and-middle income countries including South Africa, data access in health facilities is restricted due to patient privacy and confidentiality policies. Further, since clinical data is unique to individual institutions and laboratories, there are insufficient data annotation standards and conventions. As a result of the scarcity of textual data, natural language processing (NLP) techniques have fared poorly in the health sector. A cause of death (COD) is often determined by a verbal autopsy (VA) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…On more recent works that incorporate context and character information, Yan et al [58] achieved recall scores of 0.6990 while Manaka et al [79] gave 0.6000. Considering the improvement added by character information on improving COD classification, Manaka et al [49] added features from multiple domains and reported a score of 0.8755. These findings suggest that our proposed transfer learning methodology can adapt to VA datasets across various demographics as the works compared against used VA datasets collected in other developing countries, including Ghana, India and Tanzania.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On more recent works that incorporate context and character information, Yan et al [58] achieved recall scores of 0.6990 while Manaka et al [79] gave 0.6000. Considering the improvement added by character information on improving COD classification, Manaka et al [49] added features from multiple domains and reported a score of 0.8755. These findings suggest that our proposed transfer learning methodology can adapt to VA datasets across various demographics as the works compared against used VA datasets collected in other developing countries, including Ghana, India and Tanzania.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the work by Manaka et al [49], the initial step of the Multi-Step Transfer Learning framework involves an exploratory search for models across a number of domains to identify the one that best represents the VA corpus. Three sets of ELMo language models were trained in three different domains, with the objective of identifying the optimal text representations for the VA language modeling task.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations